2011
DOI: 10.1007/s10096-011-1200-7
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high prevalence of multidrug resistant tuberculosis in Murmansk, Russia: a population-based study

Abstract: Drug resistance and molecular epidemiology of tuberculosis (TB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Beijing family was the predominant genotype among the 58 XDR-TB isolates, correlating with reports from Beijing [7] and other regions of the world [4,28,29]. The modern Beijing sublineage constituted the majority (70.5%) of Beijing family strains.…”
Section: Discussionsupporting
confidence: 69%
“…Beijing family was the predominant genotype among the 58 XDR-TB isolates, correlating with reports from Beijing [7] and other regions of the world [4,28,29]. The modern Beijing sublineage constituted the majority (70.5%) of Beijing family strains.…”
Section: Discussionsupporting
confidence: 69%
“…Studies in Russia (54) and Ukraine (55) found that rpoB531 was highly prevalent in strains of the Beijing genotype. In contrast, we found no significant association between the genotype and any resistance-conferring mutation, including rpoB531.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a 74.8% rate of prevalence of the Beijing family in the studied population was found (compared to an average 50% rate among pulmonary TB patients across Russia [16,27,[36][37][38][39][40][41][42][43][44][45][46][47][48]). At the same time, the rate of B0/W148 in the Beijing population was 30% (35).…”
Section: Virulence and Transmissibilitymentioning
confidence: 99%